Human Neuroimmune Response Against Angiostrongylus Cantonensis - Gómez-Pérez, David; Meijides-Mejías, Christian Meijides-Mejías; Dorta-Contreras, Alberto Juan (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Angiostrongylus cantonensis is a zoonotic pathogen that causes human angiostrongyliasis; its main clinical manifestation is eosinophilic meningitis. It was reported in Cuba for the first time in America. Objective: To review the main immunological findings about the human neuroimmune response against this parasite. Materials and methods: This paper is based on a review of the papers mainly from Cuban authors published in the last 10 years about the human neuroimmune response against this helmint. This information becomes more relevant after the introduction of the African giant snail Lissachatina fulica in Cuba in 2014. Results: The humoral immune response is based on the immunoglobulin intrathecal synthesis. When the third-stage larvae goes to the central nervous system at the first lumbar puncture there are no major immunoglobulin synthesis. One week later an immune intrathecal response is done by a two class major immunoglobulin class mainly IgG+ IgA. Intrathecal activation of complement is evident of intrathecal synthesis of major immunoglobulins during this disease. The activation of complement system components in cerebrospinal fluid is relevant to the understanding of this tropical disease, which is emerging in the Western hemisphere. Intrathecal synthesis of at least one of the major immunoglobulins and a wide spectrum of patterns may be observed. Although intrathecal synthesis of C3c and IgE is always present, C4 intrathecal synthesis does not occur in every patient. The diversity of intrathecal synthesis and activation of the different complement pathways enables their division into three variant groups. In each one could be find the activation of one or several complement pathways including the participation of MBL, MASP-2 and ficolins as part of the lectin pathway complement activation. Conclusion: The neuroimmune response against Angiostrongylus cantonensis eosinophilic meningoencephalitis is an example of the host-parasite interaction.